A glass full of optimism: enrichment effects on cognitive bias in a rat model of depression - Richter, Sophie Helene; Schick, Anita; Gass, Peter; Vollmayr, Barbara (Cognitive, affective, & behavioral neuroscience, 2012)
Investigations of cognitive biases in animals are conceptually and translationally valuable because they contribute to animal welfare research and help to extend and refine our understanding of human emotional disorders, where biased information processing is a critical causal and maintenance factor. We employed the “learned helplessness” genetic rat model of depression in studying cognitive bias and its modification by environmental manipulations. Using a spatial judgment task, responses to ambiguous spatial cues were assessed before and after environmental enrichment to test whether this manipulation would cause an optimistic shift in emotional state. Twenty-four congenitally helpless and nonhelpless male rats were trained to discriminate two different locations, “rewarded” versus “aversive.” After successful acquisition of this spatial discrimination, cognitive bias was probed by measuring responses to three ambiguous locations. Latencies to “reach” and to actively “choose” a goal pot were recorded alongside exploratory behaviors. An overall strain difference was observed, with helpless rats displaying longer “reach” latencies than nonhelpless rats. This implies a “pessimistic” response bias in helpless rats, underscoring their depressive-like phenotype. No strain differences were observed regarding other behavioral measures. Half of the animals were then transferred to enriched cages and retested. Environmental enrichment resulted in reduced “choose” latencies in both rat strains, associating enrichment with more optimistic interpretations of ambiguous cues. Our results emphasize the suitability of cognitive bias measurement for animal emotion assessment. They extend the methodological repertoire for characterizing complex phenotypes and bear implications for animal welfare research and for the use of animal models in preclinical research.